Management of Type 2 Bubble Formed During Big Bubble Deep Anterior Lamellar Keratoplasty. Issue 2 (February 2019) - Goweida, Mohamed Bahgat; Ragab, Ahmed Mahmoud; Liu, Christopher
Abstract : Purpose: To review the outcome of 3 techniques for managing type 2 bubbles (between Descemet's membrane [DM] and stroma) formed during big bubble (BB) deep anterior lamellar keratoplasty (DALK) in different corneal pathologies. Methods: This is an interventional case series study of patients with type 2 bubbles formed during BB DALK. Three techniques to complete DALK are described: the first is a DM baring technique similar to Anwar's BB technique, the second is the microbubble incision technique to preserve the pre-Descemetic support to DM, and the third is done in eyes with combined type 1 and type 2 BB (mixed bubble), where the type 1 bubble is opened and surgery is completed avoiding the type 2 bubble. Results: Thirty-one eyes of 31 patients were included. The DM baring technique has a high rate of conversion to penetrating keratoplasty (12 of 16 eyes). In the other 2 techniques (which did not bare DM), DALK could be completed in all 15 cases with intact DM. Double anterior chamber is a relatively common complication after type 2 BB, even with an intact DM. Conclusions: DM baring techniques should be avoided in eyes with type 2 BB. Instead, deep stromal dissection searching for an incomplete type 1 bubble or using one of the manual dissection techniques as a guide to the clear pre-Descemetic stroma is safer and more reliable.